Ecotourism in the Kakum Conservation Area, Ghana: Local politics, practice and outcome. (December 2017) - Cobbinah, Patrick Brandful; Amenuvor, Daniel; Black, Rosemary; Peprah, Charles
Abstract: In many rural areas of Africa, creation of protected areas and introduction of ecotourism result in changes in local livelihoods. Yet, despite assurances of improved and alternative livelihood options by conservationists and governments, rural communities often tend to be worse-off following creation of protected areas and introduction of tourism products due to, among others, inequity in the distribution of tourism benefits. This paper examines the outcome of ecotourism in local communities adjacent to Ghana's foremost and most popular ecotourism destination – the Kakum Conservation Area – and its influence on the relationship between local residents and park officials. Using agency consultations, in-depth interviews with residents from four selected communities and document reviews, findings indicate limited ecotourism benefits and widespread ecotourism costs in the local communities in the vicinity of the Conservation Area, despite increasing tourist visitation and revenue from ecotourism to the government and the management agencies. Management implications: The likelihood to achieve benefits for the local communities in and around protected areas by ecotourism increases, If the management focuses on the pro-poor aspects and ensures that the implementation of ecotourism is not only focused on conservation goals. If the overall goals go beyond government and conservation agencies interest and include the improvement of livelihood outcomes in the local community. If the local community realises its role and participates actively. If the participation is associated with local empowerment in, and stewardship of ecotourism activities.